1996
DOI: 10.3382/ps.0750695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breeder Hen Age and Dietary Fat on Embryonic and Neonatal Broiler Serum Lipids and Glucose ,

Abstract: In two experiments, the effects of dietary fat and breeder hen age on relative yolk sac weight (RYSW) and total serum cholesterol (CHOL), high (HDLC) and low (LDLC) density lipoprotein cholesterol, triglycerides (TRI), and glucose (GLU) were monitored in broiler embryos and chicks. In Experiment 1, embryos at 18 d of incubation and chicks at hatch were sampled from eggs laid by breeder hens at 26 (young), 36, and 48 wk of age. No dietary effects were noted in either experiment; however, chicks from young hens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Raji (2000) showed the blood glucose levels of Japanese quails was affected by age. Other authors verified high cholesterol and low glucose levels in the sera of newly-hatched chicks (Latour et al, 1996;Vieira & Moran, 1999;Peebles et al, 2004), which may be explained by the transition from yolkderived lipid to dietary-based carbohydrate as primary source of energyin broilers chicks during first 2-3 days after hatch. Vieira & Moran (1999) demonstrated that the yolk sac contents are rich in fats and proteins, but are very poor in carbohydrates.…”
Section: Discussionmentioning
confidence: 84%
“…Raji (2000) showed the blood glucose levels of Japanese quails was affected by age. Other authors verified high cholesterol and low glucose levels in the sera of newly-hatched chicks (Latour et al, 1996;Vieira & Moran, 1999;Peebles et al, 2004), which may be explained by the transition from yolkderived lipid to dietary-based carbohydrate as primary source of energyin broilers chicks during first 2-3 days after hatch. Vieira & Moran (1999) demonstrated that the yolk sac contents are rich in fats and proteins, but are very poor in carbohydrates.…”
Section: Discussionmentioning
confidence: 84%
“…Incubation parameters are highly dependent on the breeder flock age (Mather and Laughlin, ; Noble et al., ; O'Sullivan et al., ; Latour et al., ). In the present study, all parameters were affected by breeder flock age, except mid‐embryonic mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples from each treatment replicate were analyzed for TG, CHOL, GLU, VLDLC, LDLC, and HDLC using an Ektachem DT-60 analyzer 7 as described by (Latour et al, 1996).…”
Section: Lipoprotein and Glucose Analysesmentioning
confidence: 99%